The Emerging Workcation Trend in Indonesia: A Preliminary Study on the Demographic Profiles, Motivations, and Experiences of Workcationers - Kurniasari, Meta Indriyani; Isbah, M. Falikul; Azca, Muhammad Najib (Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
This study investigates the trends of workcation in Indonesia, and the motivations and expectations of workcationers. Workcation is a new way of working that has gained momentum globally, including in Indonesia, particularly since the COVID-19 pandemic. However, research on the workcation trend involving Indonesian workers is limited, if not non-existent. Thus, this study aims to identify the profiles of those who adopt this work style, their motivation, preferences, and experiences. The data in this paper were drawn from an online survey and interviews with workcationers. We use a mixed method and adopt the New Ways of Working (NWW) approach to the sociology of work to provide new insights into the emerging workcation trend in the digital age. The findings show that Indonesian workers who adopt this work style are mostly millennials employed in the formal sectors and earn above the regional minimum wage. They believe that workcation can improve well-being and productivity. However, this trend has drawbacks for workers, such as alienation due to a low sense of belonging, depression, and work-life imbalance. Based on these findings, we propose some relevant social policy responses.